2016
DOI: 10.1016/j.juro.2015.12.073
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Treatment of Vesicourethral Stenosis after Radical Prostatectomy: Outcomes and Predictors of Success

Abstract: Most patients with vesicourethral stenosis after radical prostatectomy are treated successfully with endoscopic modalities but often require multiple procedures. Unlike anterior urethral strictures, in this specific scenario the use of repeat endoscopic treatments appears justified. Holmium laser incision may be more successful compared to other endoscopic modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 27 publications
1
32
0
3
Order By: Relevance
“…Consistent with the literature, patients suffering from VUS were treated successfully in 40.2% of cases (35 of 87) ( 24 , 28 ). The mean time from initial therapy to stenosis was a bit longer than for BNS, but not significantly so.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Consistent with the literature, patients suffering from VUS were treated successfully in 40.2% of cases (35 of 87) ( 24 , 28 ). The mean time from initial therapy to stenosis was a bit longer than for BNS, but not significantly so.…”
Section: Discussionsupporting
confidence: 78%
“…However, the success rate after repeat endoscopic therapies decreases. Some studies have shown a declining success rate after repeated transurethral surgery ( 24 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…LaBossiere and colleagues published the largest series to date comparing endoscopic modalities used to treat VUAS in 142 patients. 47 In the holmium laser group, the fibrotic tissue was incised using a holmium laser at the 3 and 9 o'clock positions and an [18][19][20] Cold-or hot-knife incisions. Stenosis incision with either a cold or hot knife has also been used to successfully treat VUAS with comparable outcomes to holmium laser incision in many series.…”
Section: Endourologic Treatmentmentioning
confidence: 99%
“…The latter one, is a rare but troublesome complication with an incidence of approximately 8.4% (5-10). It's well known that the endoscopic approach provides good results; success rates vary from 50 to 91% with a mean of 2.1 interventions per patient (2, 11, 12).…”
Section: Introductionmentioning
confidence: 99%